2008
DOI: 10.1098/rspb.2008.1131
|View full text |Cite
|
Sign up to set email alerts
|

Human-mediated dispersal of seeds over long distances

Abstract: Human activities have fundamental impacts on the distribution of species through altered land use, but also directly by dispersal of propagules. Rare long-distance dispersal events have a disproportionate importance for the spread of species including invasions. While it is widely accepted that humans may act as vectors of long-distance dispersal, there are few studies that quantify this process. We studied in detail a mechanism of human-mediated dispersal (HMD). For two plant species we measured, over a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
191
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(198 citation statements)
references
References 53 publications
(83 reference statements)
5
191
1
1
Order By: Relevance
“…The movements of wetland birds within and between catchments shape the dispersal pattern of many hydrophilic plants (Amezaga et al 2002;Figuerola and Green 2002;). Wichmann (2009) demonstrated that seeds that were dispersed by wind maximally 250 m were carried by walking humans up to 10 km (cf. Auffret and Cousins 2013).…”
Section: Appendixmentioning
confidence: 99%
“…The movements of wetland birds within and between catchments shape the dispersal pattern of many hydrophilic plants (Amezaga et al 2002;Figuerola and Green 2002;). Wichmann (2009) demonstrated that seeds that were dispersed by wind maximally 250 m were carried by walking humans up to 10 km (cf. Auffret and Cousins 2013).…”
Section: Appendixmentioning
confidence: 99%
“…The 'hot spots' usually occur under 'bird cliffs' and are enriched by nutrients and characterized by higher insulation and protected against strong winds. Another potential source of diaspores is the regular boat service during the summer, which brings about 30 tourists per day to the former settlement (Wichmann et al 2009;Hall et al 2010). …”
Section: Risk Assessment and Monitoring Prioritiesmentioning
confidence: 99%
“…Feral oilseed rape typically originates either from the spillage of seed during its transport to and from fields, the redistribution of seed by field equipment (Price et al, 1996;Zwaenepoel et al, 2006;von der Lippe and Kowarik, 2007b;Pivard et al, 2008a,b), or the dispersal of seed, for example by birds and mammals (von der Lippe and Kowarik, 2007a,b;Wichmann et al, 2009). Within agricultural fields, seeds can be lost through the shattering of the seed-bearing pods before and during harvest.…”
Section: Definition and Sourcesmentioning
confidence: 99%
“…Seed brought in from outside could be carried by vehicles, road verge mowers, animals, or by the movement of soil for agricultural and building works (Wilkinson et al, 1995;Garnier et al, 2008;Wichmann et al, 2009). Garnier et al (2008 showed that wind turbulence behind passing vehicles locally contributed to the secondary dispersal of seed: on average, 20% of the seed was estimated to disperse over a few metres, while 80% of the seed remained at the original place.…”
Section: Redistribution Of Feral Seed Between Local Populations Versumentioning
confidence: 99%